TEACHING WRITING DESCRIPTIVE TEXTS USING CONCEPT MAP OF GRAPHIC ORGANIZER - Riani, Bela; Sudarsono, Sudarsono; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted to find out the effect of using concept map of graphic organizer on teaching writing descriptive text. The population of this research was all of Year ? 8 students of SMP Negeri 7 Sungai Raya KabupatenKubu Raya in Academic Year 2018/2019, and the writer took the sample by using lottery from Year ? 8 Class D which consist of 28 students. The writer conducted this research through pre-experimental research with one group pre-test and post-test design. The writer collected the data using a measurement technique to measure students writing descriptive text, and the writer used an essay form which consists of instructional objectives. The findings showed that the students? mean score of pre ? test was 49.07 and after the treatment, students? mean score of post ? test was 67.86. Therefore, the finding also showed the result of the t-test was 17.56 that higher than t-table 2.052 with ?=0.05. It showed that null hypothesis (HO) is rejected and the alternative hypothesis (Ha) that the use of concept map does affect the teaching of writing descriptive text is accepted. In conclusion, concept map of graphic organizer was significantly affects students? writing in descriptive text.Key Words: Writing, Descriptive Texts, Concept Map